Dual mechanical and pharmacological thromboprophylaxis decreases risk of pulmonary embolus after laparotomy for gynecologic malignancies. Issue 1 (22nd June 2020) - Nguyen, Julie My Van; Gien, Lilian T; Covens, Allan; Kupets, Rachel; Osborne, Raymond J; Sadeghi, Mahsa; Nathens, Avery B; Vicus, Danielle
Abstract : Objectives: Patients with gynecologic malignancies have high rates of post-operative venous thromboembolism. Currently, there is no consensus for peri-operative thromboprophylaxis specific to gynecologic oncology. We aimed to compare rates of symptomatic pulmonary embolus within 30 days post-operatively, and to identify risk factors for pulmonary embolus. Methods: The Division of Gynecologic Oncology at Sunnybrook Health Sciences Centre implemented dual thromboprophylaxis for laparotomies in December 2017. We conducted a prospective study of laparotomies for gynecologic malignancies from December 2017 to October 2018, with comparison to historical cohort from January 2016 to November 2017 using the institutional National Surgical Quality Improvement Program database (NSQIP). Pre-intervention, patients received low molecular weight heparin during admission and extended 28-day prophylaxis was continued at the surgeon's discretion. Post-intervention, all patients received both mechanical thromboprophylaxis with sequential compression devices during admission and 28-day prophylaxis with low molecular weight heparin. Results: There were 371 and 163 laparotomies pre- and post-intervention, respectively. Patient characteristics (age, body mass index, diabetes, smoking, tumor stage), rate of malignant cases, operative blood loss and duration, and length of stay were similar between groups. After implementation, pulmonary emboli rates decreased from 5.1% to 0% (p=0.001). There were more cytoreductive procedures pre-intervention (p≤0.0001) but surgical complexity scores were similar (p=0.82). Univariate analysis revealed that surgery pre-intervention (OR 4.25, 95% CI 1.04 to 17.43, p=0.04), length of stay ≥5 days (OR 11.94, 95% CI 2.65 to 53.92, p=0.002), and operative blood loss ≥500 mL (OR 2.85, 95% CI 1.05 to 7.8, p=0.04) increased risk of pulmonary embolus. On multivariable analysis, surgery pre-intervention remained associated with more pulmonary emboli (OR 4.16, 95% CI 1.03 to 16.79, p=0.045), when adjusting for operative blood loss. Conclusion: Dual thromboprophylaxis after laparotomy significantly reduced rates of pulmonary embolus in this high-risk patient population.